Progress of Research on Welding for Molybdenum Alloys - Wang Jiteng; Wang Juan; Li Yajiang; Zheng Deshuang (High Temperature Materials and Processes, 2014)
Molybdenum and molybdenum alloys are considered to be attractive structural materials for high-temperature applications. However, molybdenum alloys are sensitive to gas impurities and have the characteristics of low temperature embrittlement and less resistance to oxidation at elevated temperature. The toughness and strength of welded joint is not easy to be ensured by traditional technology. Recently, many efforts have been made to join molybdenum and its alloys. In this paper, we present the result of investigations on welding methods of molybdenum and its alloys and overview the practical applications in engineering. The key of joining molybdenum alloys is to improve the toughness of welded joint and prevent the generation of pores and cracks.